Voter Turnout and the Dynamics of electoral Competition in Etablished Democracies since 1945 - Franklin, Mark N (Cambridge University Press, 2004)
This book shows how voter turnout can serve as an indicator of the health of a democracy. It enumerates conditions that can result in low voter turnout and suggests reforms that might alleviate these conditions. Its innovative finding is that declining turnout does not reflect reductions in civic virtue or increases in alienation. Turnout falls, when it does, because of cumulating effects of institutional changes, because elections lack competitiveness, or because a larger proportion of the electorate pays attention to this lack of competitiveness.